Determinants of Accounting Students' Perceptions of Earnings Management Practices with the Level of Ethical Knowledge - Rinaia, Syafia; Jurana, Jurana; Din, Muhammad; Paranoan, Selmita (Equity: Jurnal Akuntansi, 2024)
Phenomena related to earnings management practices raise ethical dilemmas, especially for accounting students. This research aims to analyze the influence of the ethical orientation of idealism and relativism on accounting students' perceptions regarding earnings management practices with the level of ethical knowledge as a moderating variable. The research was conducted on accounting students at Tadulako University from July to September 2023 with a sample size of 267, with PLS analysis. The research results prove that the influence of idealism has no effect on accounting students' perceptions regarding earnings management practices. Relativism has a positive effect on accounting students' perceptions regarding earnings management practices. The level of ethical knowledge strengthens the influence of idealism and relativism on accounting students' perceptions regarding earnings management practices. Idealism and relativism have a positive simultaneous effect on students' perceptions regarding earnings management practices. Therefore, the results of this research can be used as a reference for academics so that in the learning process they can incorporate ethical values into each lesson and conduct case study discussions regarding accounting scandals that occurred.